Interactive Procedural Knowledge Learning Resources Development in The Context of Competency-Based Training Instructional Approach and Interactive Media Design Subjects for Information Technology Vocational High School - Herlambang, Admaja Dwi; Budiman, Baiti; Wardhono, Wibisono Sukmo (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
Many research has proven the good impact of digital learning resources on the knowledge acquisition by students. However, this research only focuses on factual and conceptual knowledge types. In contrast, the learning process in vocational high schools is dominated by procedural knowledge and practical activities. This research aims to produce a digital handbook appropriate in content, media, and utilization in the learning process of procedural knowledge at an information technology vocational high school. Digital handbook components were arranged based on the context of the Competency-Based Training (CBT) instructional approach and Interactive Media Design subjects. The digital handbook was developed under the Four-D model dan Cognitive Theory of Multimedia Learning. The content, media, and practicality appraisal were carried out to prove that the digital handbook is appropriate as a digital learning resource. The material, media, and practicality appraisal involves subject matter experts, multimedia learning experts, and potential users. The content validity average score is 97.80%, the media validity score is 95.50%, and the practicality score is 90.00%. Based on these, the digital handbook is declared practical and worth using as an interactive digital learning resource for procedural knowledge, potentially attracting students to hands-on or practical activities and guiding students to learn independently.